Estrategias de intervención temprana para mejorar la competencia matemática en niños de educación inicial. - Toapanta Silva, Paolo Fernando (2025)
Learning mathematics in early education is fundamental, since it promotes effective learning in this area. Thus, the objective is to identify the activities that promote essential mathematical skills in children from 3 to 5 years of age. To achieve this objective, a qualitative methodology was used, based on an exhaustive analysis of previous research on pedagogical interventions focused on mathematics teaching. These results revealed that play activities, the use of manipulatives and curricular integration are key tools to facilitate mathematical learning at this stage. Playful activities, such as mathematical games, not only help in the acquisition of mathematical skills, but also promote social interaction and collaboration. Aspects that are relevant for their formation. The use of manipulatives, such as blocks and beads, allows children to visualize and understand abstract concepts, helping them to establish connections between the concrete and the abstract. On the other hand, the integration of this subject in other areas was also identified as an effective strategy. Finally, it was found that teacher training is crucial to implement these strategies effectively in the classroom, since adequate training allows for the improvement of mathematical competencies.